Selenium: a critical chemical element in nano and quantum physics - G. Guisbiers (Advances in Physics: X)
Selenium is a chemical element from the chalcogenide group (Oxygen, Sulfur, Selenium and Tellurium), which has been defined as a critical element by the American Physical Society and the Materials Research Society. Indeed, selenium is used abundantly in nanotechnologies but its scarcity on Earth put its sustainability at risk. This review highlights the properties of selenium at the nanoscale and illustrates some of its most important applications in medicine, agriculture, catalysis, opto-electronics, photovoltaics, piezo-electrics and quantum electronics.